Implementasi Sistem Online Single Submission Risk Based Approach (OSS-RBA) dalam Pelayanan Mendirikan Izin Usaha di Dinas Penanaman Modal dan Pelayanan Terpadu Satu Pintu Kabupaten Merauke - Khoriyatun (Jurnal Administrasi Karya Dharma, 2025)
This research aims to implement the Online Single Submission Risk Based Approach (OSS-RBA) System and provide understanding to the public in using the system (OSS-RBA). The method used is a descriptive method, while the approach in this research uses a qualitative approach and data analysis techniques use three stages of Data Reduction, Data Presentation and Conclusion Drawing. From the results of the research conducted, there are several shortcomings that can hinder the operation of the Online Single Submission Risk Based Approach (OSS-RBA) System, namely a lack of public understanding regarding the science of information technology and related use of the system (OSS-RBA), a system that continues to be regularly maintained, a lack of information and outreach to the public, and the application of regulations regarding permits that continue to undergo changes that can affect the process of making business permits. The Merauke Regency One Stop Integrated Investment Service is basically running well and is supported by competent human resources in mastering everything from system operations to education and a structured implementation process.